Evaluation of ship’s green degree using a novel hybrid approach combining group fuzzy entropy and cloud technique for the order of preference by similarity to the ideal solution theory - Liu, Xu; Tian, Guangdong; Fathollahi-Fard, Amir Mohammad; Mojtahedi, Mohammad (Clean technologies and environmental policy, 2020)
The pollution and emission caused by the manufacturing, operation, and scrapping of marine ships have considerable impact on the environment. Therefore, it is essential to develop an effective and efficient approach toward evaluating the environmental impact of ships. This study uses the green degree of ships concept to evaluate different alternatives. Because environmental evaluation involves several criteria, the problem can be formulated as a traditional multi-criteria decision-making (MCDM) model. In this regard, the main innovation of this study is the development of an improved MCDM model using a novel hybrid method, namely the group fuzzy entropy and cloud technique for order of preference by similarity to ideal solution theory. The developed model calculates the criteria weight and rank based on the selected criteria and alternatives. Finally, a criteria system is developed to evaluate several classical alternatives, and various sensitivity analyses were carried out to validate the robustness of the proposed methodology. The results revealed that the model and criteria system can provide several quantitative and qualitative indicators for governmental policy-makers and agencies, environmental consultants, and environmental service organizations. Graphic abstract